2003
DOI: 10.1097/01.ju.0000051480.62175.35
|View full text |Cite
|
Sign up to set email alerts
|

TNM T3a Renal Cell Carcinoma: Adrenal Gland Involvement is Not the Same as Renal Fat Invasion

Abstract: Upper pole tumors with direct extension into the adrenal gland predict significantly worse survival than similarly staged tumors with fat invasion and they have a prognosis similar to that of stage pT4 disease. While these data await external validation, consideration should be given to re-categorizing tumors with direct adrenal gland involvement as stage pT4 or in a subcategory such as pT4a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 15 publications
5
57
0
7
Order By: Relevance
“…89,90 In the 2002 edition of the TNM classification both direct infiltration of the adrenal gland and infiltration into perirenal fat remain classified as category T3a. From published series this would appear inappropriate as patients with direct extension of tumor into the adrenal gland have been shown to have a poor prognosis, with 5-year survival of 20.2% being similar to that for pT4 tumors.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…89,90 In the 2002 edition of the TNM classification both direct infiltration of the adrenal gland and infiltration into perirenal fat remain classified as category T3a. From published series this would appear inappropriate as patients with direct extension of tumor into the adrenal gland have been shown to have a poor prognosis, with 5-year survival of 20.2% being similar to that for pT4 tumors.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…[7][8][9][10] Therefore, in the revised 2010 TNM staging system, direct adrenal gland invasion was reclassified into the T4 stage. Our results were consistent with those of previous studies and supported this revision.…”
Section: Discussionmentioning
confidence: 99%
“…Because of a small number of patients and based on several reports demonstrating that patients with direct invasion of the adrenal gland have survival comparable to those with tumors involving adjacent organs (pT4 disease), patients with direct adrenal gland invasion were excluded from analyses. 5,7,15 Kaplan-Meier analyses of the risk groupings in the pT3 2002 AJCC primary renal tumor classification revealed decreased disease-specific survival in pT3b patients compared with pT3a RCC patients. Trend analysis revealed that, taken as a whole, the pT3 2002 AJCC RCC classification did not effectively stratify patients according to their risk of death from RCC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 Recently, several centers have clearly demonstrated that tumors with direct ipsilateral invasion of the adrenal gland should be staged as pT4 because they behave more aggressively than tumors involving perinephric or renal sinus fat. [5][6][7] Moreover, controversy exists regarding the prognostic significance of the cranial extension of venous tumor thrombus (VTT), the location of extrarenal extension (ERE), and the concomitant presence of both pathologic features. [8][9][10][11][12][13] By examining the prognostic features and cancerspecific outcomes of a large cohort of patients treated within the past 15 years for RCC at a tertiary referral center, this study seeks to reassess and suggest possible improvements to the 2002 AJCC pT3 classification of RCC.…”
Section: Resultsmentioning
confidence: 99%